A third way: Developing a planetary spirituality. Issue 1 (6th March 2018) - Bauman, Whitney A.
Abstract: Globalization has brought the world closer together, but it has come with a cost. Over the past several decades, it seems our only two options for moving ahead are through continued globalization of a neoliberal model of economics as usual, or some sort of return to nationalism. Many countries are facing the challenges of globalization and opting for one or the other of these models to deal with a globalized world. Might there be a third way? Perhaps religious leaders can help bring about a third, planetary model that helps us to navigate between the ills of neoliberalism and nationalism, and toward an understanding of a planetary vision of spirituality, ethics, and citizenship.